CYBERSPACE ETHICS: FINDING AN EQUILIBRIUM BETWEEN FREEDOM AND PROTECTIONISM - Haekal, AL ASYARI; Arifin, Muhammad Ardiansyah; Grace, Yosephine (Lex et scientia, 2023)
Cyber freedom refers to an approach at regulating cyberspace that opposes state monopoly over cyberspace regulatory making. A compelling argument for this concept could be argued by the nature of the most known cyberspace instrument: the internet. According to Lessig, the internet was designed for research, not the concealment of information. In the meantime, many states believe that limiting the cyberspace is a way forward. By exercising jurisdiction to constituting cyberspace facilities, data governance, and cyber operations, the sovereign will be able to protect cyberspace from harm and unnecessary chaos. Practically put, states are divisive in adopting between favouring a multistakeholder approach and a government centred authority. Despite owing the nature of cyberspace to be borderless and limitless, human beings are still the inherent subject and bearer of responsibility and liability of every conduct in cyberspace. Human naturally possess values of norms and ethics. As the creator and centrepiece of every activity in the virtual world, cyberspace is built on the foundations of ethics. The priority to serve basic human needs, respect for privacy and freedom, equality, and inclusivity, as well as to protect and not destroy are the four-fundamental ethics of cyberspace. This article attempts to validate the existence of those ethics, despite the different normative approaches each state may adopt. To that end, it also suggests an innocent proposal to how the freedom of cyberspace may be limited, and how the protectionist is able to unshackle restrictions to position cyberspace on a purposive scale for every human need.